Optimal approach for diagnosing peripheral lung nodules by combining electromagnetic navigation bronchoscopy and radial probe endobronchial ultrasound - Bora Lee; Hee Sang Hwang; Se Jin Jang; Sang Young Oh; Mi Young Kim; Chang‐Min Choi; Wonjun Ji (Thoracic Cancer, 2024)
Abstract Introduction Electromagnetic navigation bronchoscopy (ENB) and radial probe endobronchial ultrasound (RP‐EBUS) are essential bronchoscopic procedures for diagnosing peripheral lung lesions. Despite their individual advantages, the optimal circumstances for their combination remain uncertain. Methods This single‐center retrospective study enrolled 473 patients with 529 pulmonary nodules who underwent ENB and/or RP‐EBUS biopsies between December 2021 and December 2022. Diagnostic yield was calculated using strict, intermediate, and liberal definitions. In the strict definition, only malignant and specific benign lesions were deemed diagnostic at the time of the index procedure. The intermediate and liberal definitions included additional results from the follow‐up period. Results The diagnostic yield of the strict definition was not statistically different among the three groups (ENB/Combination/RP‐EBUS 63.8%/64.2%/62.6%, p = 0.944). However, the diagnostic yield was superior in the ENB + RP‐EBUS group for nodules with a bronchus type II or III and a solid part <20 mm (odds ratio 1.96, 95% confidence interval 1.09–3.53, p = 0.02). In terms of complications, bleeding was significantly higher in the ENB + RP‐EBUS group (ENB/Combination/RP‐EBUS 3.7% /6.2/0.6%, p = 0.002), but no major adverse event was observed. Conclusion The combination of ENB and RP‐EBUS enhanced the diagnostic yield for nodules with bronchus type II or III and solid part <20 mm, despite a slightly elevated risk of bleeding. Careful patient selection based on nodule characteristics is important to benefit from this combined approach.